Proceedings of the 17th International Conference on Virtual-Reality Continuum and Its Applications in Industry 2019
DOI: 10.1145/3359997.3365751
|View full text |Cite
|
Sign up to set email alerts
|

Mixing realities for sketch retrieval in Virtual Reality

Abstract: Drawing tools for Virtual Reality (VR) enable users to model 3D designs from within the virtual environment itself. These tools employ sketching and sculpting techniques known from desktopbased interfaces and apply them to hand-based controller interaction. While these techniques allow for mid-air sketching of basic shapes, it remains difficult for users to create detailed and comprehensive 3D models. In our work, we focus on supporting the user in designing the virtual environment around them by enhancing ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…They gather handdrawn 3D sketches and generate a dataset paired with a 3D model collection. Giunchi et al [18,20,21] implemented a VR application that uses sketch as the main mechanism to search a target chair among an extensive collection. This software provides the user with an iterative method of depicting a chair, querying a neural network with a 3D sketch at each step, or by fusing the sketch and a chair model.…”
Section: Sketch In Mixed Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They gather handdrawn 3D sketches and generate a dataset paired with a 3D model collection. Giunchi et al [18,20,21] implemented a VR application that uses sketch as the main mechanism to search a target chair among an extensive collection. This software provides the user with an iterative method of depicting a chair, querying a neural network with a 3D sketch at each step, or by fusing the sketch and a chair model.…”
Section: Sketch In Mixed Environmentmentioning
confidence: 99%
“…In contrast, 3D sketch as query-by-example is an under-explored research area in the context of virtual environments. Recent works have shown that 3D sketch alone does not lead to high accuracy results [18]. Giunchi et al [19] address this issue by presenting the user with a navigable set of query results instead of a single one.…”
Section: Introductionmentioning
confidence: 99%
“…They gather hand-drawn 3D sketches and generate a dataset paired with a 3D model collection. Giunchi et al [18,20,21] implemented a VR application that uses sketch as the main mechanism to search a target chair among an extensive collection. This software provides the user with an iterative method of depicting a chair, querying a neural network with a 3D sketch at each step, or by fusing the sketch and a chair model.…”
Section: Sketch In Mixed Environmentmentioning
confidence: 99%
“…In contrast, 3D sketch as query-by-example is an under-explored research area in the context of virtual environments. Recent works have shown that 3D sketch alone does not lead to high accuracy results [18]. Giunchi et al [19] address this issue by presenting the user with a navigable set of query results instead of a single one.…”
Section: Introductionmentioning
confidence: 99%